CURRENT ISSUES OF MODERN LINGUISTICS AND TRANSLATION (Web of Teachers: Inderscience Research, 2025)
This paper explores contemporary challenges in the field of linguistics and translation studies. With the increasing influence of globalization, artificial intelligence, and multilingual digital communication, the demands placed on linguists and translators have evolved significantly. The article presents current theoretical debates, practical applications, and statistical trends, highlighting the pressing issues faced by professionals and researchers in both fields.